Principles of Ukrainian medical terminology for the lexical-semantic level (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article discusses and analyzes the problematic aspects in the creation and functioning of the Ukrainian medical terms in the lexical-semantic level.
Keywords: Ukrainian medical terminology; polysemy (multiple meanings); homonymy; paronimiya; antonyms; synonyms; , borrowing (foreign language terms) actually specific vocabulary